Is Health Insurance Crippling the Labor Market? - Douglas Holtz-Eakin (Levy Economics Institute of Bard College, 1993)
While discussion about health care encompasses a wide array of issues-inadequate access, the growing share of national resources devoted to health care, the incidence of cost-shifting from the uninsured to the insured, and differences in premium costs between seemingly similar insured individuals-growing significance has been placed on how aspects of the current system may create distortions in the labor market. Some of these issues are addressed in this working paper, including the extent to which labor market mobility is hampered by the nonportability of employer-provided insurance.
Keywords: 330